Comparison of Some Clinical, Hematological and Serological Parameters According to the Level of Disease Activity in Patients with Rheumatoid Arthritis - Khamees, Mays Saleh; Alasady, Raad Abdulameer (Medical Science Journal for Advance Research, 2024)
Objective: This study aimed to evaluate the usefulness of some clinical, hematological, and serological parameters in monitoring of RA activity. Methods: This study included 107 RA patients [98 females and 9 males; mean age 46.85 years (range 18–70)]. The patients were classified into four groups based on their disease activity scores. Disease activity scores (DAS-28 ESR and DAS-28 CRP), complete blood count (CBC), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF), and anti-citrullinated peptide antibody (ACPA) were measured. Results: Both “DAS-28 ESR and DAS-28 CRP” showed a significant difference among the four disease activity groups regarding family history, disease duration, regularity of treatment intake, response to treatment, and ESR level (P> 0.05). Furthermore, DAS-28 CRP revealed a significant difference (P = 0.021) in the CRP levels across the four disease activity groups. Conclusion: The study found an association between some clinical, hematological, and serological factors and the level of disease activity in patients with RA.